Management of primary headaches during pregnancy, postpartum, and breastfeeding: A systematic review. Issue 1 (12th January 2021) - Saldanha, Ian J.; Cao, Wangnan; Bhuma, Monika Reddy; Konnyu, Kristin J.; Adam, Gaelen P.; Mehta, Shivani; Zullo, Andrew R.; Chen, Kenneth K.; Roth, Julie L.; Balk, Ethan M.
Abstract: Background: Primary headaches (migraine, tension headache, cluster headache, and other trigeminal autonomic cephalgias) are common in pregnancy and postpartum. It is unclear how to best and most safely manage them. Objective: We conducted a systematic review (SR) of interventions to prevent or treat primary headaches in women who are pregnant, attempting to become pregnant, postpartum, or breastfeeding. Methods: We searched Medline, Embase, Cochrane CENTRAL, CINAHL, ClinicalTrials.gov, Cochrane Database of SRs, and Epistemonikos for primary studies of pregnant women with primary headache and existing SRs of harms in pregnant women regardless of indication. No date or language restrictions were applied. We assessed strength of evidence (SoE) using standard methods. Results: We screened 8549 citations for studies and 2788 citations for SRs. Sixteen studies (mostly high risk of bias) comprising 14, 185 patients (total) and 26 SRs met the criteria. For prevention, we found no evidence addressing effectiveness. Antiepileptics, venlafaxine, tricyclic antidepressants, benzodiazepines, β‐blockers, prednisolone, and oral magnesium may be associated with fetal/child adverse effects, but calcium channel blockers and antihistamines may not be (1 single‐group study and 11 SRs; low‐to‐moderate SoE). For treatment, combination metoclopramide and diphenhydramine may be more effective than codeine for migraine or tension headache (1 randomized controlled trial; low SoE). Triptans may not be associated with fetal/child adverse effects (8 nonrandomized comparative studies; low SoE). Acetaminophen, prednisolone, indomethacin, ondansetron, antipsychotics, and intravenous magnesium may be associated with fetal/child adverse effects, but low‐dose aspirin may not be (indirect evidence; low‐to‐moderate SoE). We found insufficient evidence regarding non‐pharmacologic treatments. Conclusions: For prevention of primary headache, calcium channel blockers and antihistamines may not be associated with fetal/child adverse effects. For treatment, combination metoclopramide and diphenhydramine may be more effective than codeine. Triptans and low‐dose aspirin may not be associated with fetal/child adverse effects. Future research should identify effective and safe interventions in pregnancy and postpartum.